The Institutionalisation of Evaluation in the Americas
XXVI, 525 p. 21 illus.
Keywords: This book examines the progress of institutionalisation of evaluation in American countries from various perspectives. It describes both prior developments and current states of evaluation in eleven countries and three transnational organisations in the Americas, focusing particularly on the political, social and professional system dimensions. These detailed country reports, which have been written by selected researchers and authors from each of the respective countries, lead to a concluding comparison and synthesis. This is the second of four volumes of the compendium The Institutionalisation of Evaluation, to be followed by volumes on Africa and Asia Pacific. The first volume on Europe was published in 2020. The overall aim is to provide an interdisciplinary audience with cross-country learning to enable them to better understand the institutionalisation of evaluation in different nations, world regions and sectors. Reinhard Stockmann is Professor of Sociology at SaarlandUniversity, Germany. He is Founder and Director of the Center for Evaluation (CEval). Wolfgang Meyer is Professor of Sociology at Saarland University, Germany and Adjunct Professor at Uganda Technology and Management University, Kampala, Uganda. Laszlo Szentmarjay is Research Associate at the Centre for Evaluation (CEval) at Saarland University, Germany. He is also Project Manager at CEval GmbH.